Bridging the GRACE gap: Validation of satellite gravity observations via glacial isostatic adjustment - Vermeulen, Sander (author) (2019)
The GRACE mission has provided unprecedented insights into mass redistribution processes in the Earth system. Following a strong call for continuation of the mass observations, the GRACE-Follow On (GRACE-FO) mission was launched in May 2018, leaving a coverage gap of ca. 1 year between GRACE and GRACE-FO. Geopotential solutions derived from data of the Swarm mission (2013-present) are candidate data to potentially bridge this gap, as well as bridge the minor discontinuities in the current GRACE time series. This study aims to validate the sensitivity of the Swarm measurement system to mass rates, by comparing GRACE and Swarm observations of the gravity trend induced by glacial isostatic adjustment (GIA). Studies inverting GIA observations (e.g., relative sea level change, surface deformation, [time variable] gravity) into mantle viscosity estimates suggest relatively high viscosity in the Hudson Bay area. This suggests that the North American GIA-induced gravity trend is linear on a multi-decadal time scale, which means we can extrapolate the GRACE-derived GIA observations into the Swarm time period for this area. We find that the Swarm-derived GIA observations correspond well in amplitude and spatial distribution to GRACE observations and conclude that both systems have a similar sensitivity to gravity trends at spatial scales to which Swarm is sensitive to (ca. 1500 km). We validate our findings via geopotential solutions of GRACE-FO and provide a brief analysis of the benefits of adding Swarm-derived information to the combined GRACE / GRACE-FO time series. Aerospace Engineering